Association between Helicobacter Pylori and Hyperemesis Gravidarum (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Hyperemesis gravidarum (HG) is the severe form of the nausea & vomiting in pregnancy and is associated with weight loss, ketonemia ,ketonuria ,electrolyte imbalances and profound volume depletion. Increased accumulation of fluid caused by elevated steroid hormones in pregnancy, a shift in pH and change of pH in the gastrointestinal tract could result in the manifestation of subclinical Helicobacter pylori (H. Pylori) infection. We therefore examined whether seropositivity for IgG antibodies to H. Pylori may be related to hyperemesis graviderum.Objective: To determine the association of H-pylori infection in hyperemesis graviderum patients.Methodology: A cross sectional study was conducted in the department of obstetrics and gynaecology, Dhaka medical college hospital from January 2007 to December 2008. Total 82 pregnant patients, 40 were hyperemesis gravidarum patients (Cases, group A) and 42 were normal pregnancy without hyperemesis graviderum (Control, group B) for admission and attending for routine ANC in OPD were selected. Purposive sampling method was followed as per inclusion and exclusion criteria. Evaluation of the patients was based on history, physical examination and investigation. Serum IgG antibody response to H.pylori antigen by ELISA were measured from every patients and analysed for its association with HG.Results: Most of the patients of this study were primi gravida, Group-A was 72.5% and Group-B was 66.7%. Maximum number of women in both the groups belonged to lower socio-economic status (Group-A was 85% and Group-B was (76%). Previous H/O hyperemesis gravidarum in the Group-A was 52.5% and Group-B was 07 % (p